2020
DOI: 10.1101/2020.05.01.20084384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Susceptible-Infected-Removed (SIR) model of COVID-19 epidemic trend in Malaysia under Movement Control Order (MCO) using a data fitting approach

Abstract: Background: In this work, we presented a Susceptible-Infected-Removed (SIR) epidemiological model of COVID-19 epidemic in Malaysia post- and pre-Movement Control Order (MCO). The proposed SIR model was fitted to confirmed COVID-19 cases from the official press statements to closely reflect the observed epidemic trend in Malaysia. The proposed model is aimed to provide an accurate predictive information for decision makers in assessing the public health and social measures related to COVID-19 epidemic. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It reduces the infected population drastically which means social distancing is a major key to face this epidemic in this scenario. A similar flattened curve pattern was also observed in Cameroon, Egypt, and Malaysia (Arifin et al . 2020, Mahmud and Lim 2020).…”
Section: Discussionsupporting
confidence: 83%
“…It reduces the infected population drastically which means social distancing is a major key to face this epidemic in this scenario. A similar flattened curve pattern was also observed in Cameroon, Egypt, and Malaysia (Arifin et al . 2020, Mahmud and Lim 2020).…”
Section: Discussionsupporting
confidence: 83%
“…The current situation has led the economy to collapse, causing severity on employment, wages, and livelihoods, undermining supply chains and upsetting industries, as well as provoking inequality, suffering and difficulties, especially among the poor Lin (2020). In Malaysia, the gross domestic product (GDP) exhibited reduction by 17.1% in the second quarter of 2020 (Arifin et al, 2020). The limited economic activity was due to restriction imposed during the MCO periods, which affected the industrial productivity in Malaysia.…”
Section: Journal Of Statistical Modeling and Analyticsmentioning
confidence: 99%
“…Department of Statistics Malaysia (DOSM) had reported that all sectors, excluding agricultural sectors, shows negative growth resulting from implementation of MCO (Arifin et al, 2020). The most affected sector was tourism, factoring from lack of international and local tourism activities.…”
Section: Journal Of Statistical Modeling and Analyticsmentioning
confidence: 99%
“…Our modelling results demonstrate that compliances of homogeneous populations show a higher overall infection, except for full compliance. This shows the importance of considering more realistic social networks like scale-free in simulations aimed at policymaking [16]. Different local and global connectivities affect the spread in different manners.…”
Section: Discussionmentioning
confidence: 99%